The three second time window in poems and language processing in general: Complementarity of discrete timing and temporal continuity. Issue 4 (26th August 2020) - Yu, Xinchi; Bao, Yan
Abstract: The existence of discrete time windows has triggered the search for permanence and continuity for artists (including poets) in multiple cultures throughout history. In this article, we argue that there exists a 3‐s window in the temporal structure of poems as well as in the aesthetic appreciation of poetry by reviewing previous literature on the temporal aspects of poems. This 3‐s window can also be considered to be a general temporal machinery underlying human behavior, including language production and perception in general. The reafference principle has provided us a unique frame for understanding cognitive processes. However, "time" was absent in the original two‐stage reafference principle. Therefore, we propose a three‐stage cycling model of language perception, taking into account time and time windows. We also inspect the possible neural implementations of the three stages: the generation, maintenance, and comparison of predictions (as well as the integration of predictions into the representational context). These three stages are embedded in a temporal window of 3 s and are repeated in a cycling mode, resulting in the representational context being continuously updated. Thus, it is possible that "semantics" could be carried forward across different time windows, being a "glue" linking the discrete time windows and thus achieving the subjective feeling of temporal continuity. Candidates of such "semantic glue" could include semantic and syntactic structures as well as identity and emotion.